Perfil epidemiológico do HIV nas gestantes atendidas pelo programa PROTEGE no estado de Sergipe no período de 2020 a 2022. - Costa, Fernanda Vasconcelos Rodrigues da; Santos-Júnior, José Hélio Fernandes; Silva, Noemí Oliveira; Telles, Ênio Pereira; Ferreira, Talita de Lima Hora; Silva, Luiz André Santos; Souza, Marilia Trindade de Santana; Souza, Carlos Adriano Santos; Santos, Cliomar Alves dos (Scire Salutis)
Objective: To investigate the epidemiological profile of vertical HIV transmission in pregnant women assisted by the PROTEGE Program in the State of Sergipe. Methods: A retrospective cross-sectional study with a sample consisting of pregnant women and newborns assisted by primary healthcare services in municipalities of the state of Sergipe, part of the PROTEGE program. Results: 51% of pregnant women with reactive HIV tests were aged 20 to 29 years during the period from 2020 to 2022. Regarding race, the majority self-identified as mixed race (42%). Most positive HIV cases were recorded in the municipality of Nossa Senhora de Glória (20%), followed by the Lagarto region (17%) and the Estância region (13%). Conclusion: It can be inferred that the tests performed are extremely important for implementing public policies related to pregnant women with HIV. Laboratory diagnosis combined with referrals for prenatal care follow-up are vital tools to prevent vertical transmission.